2016
DOI: 10.1007/s10751-016-1286-5
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of 57Fe emission Mössbauer spectroscopy to Ar and C induced defects in ZnO

Abstract: Emission Mössbauer Spectroscopy (eMS) measurements, following low fluence (<10 12 cm −2) implantation of 57 Mn (t 1/2 = 1.5 min.) into ZnO single crystals preimplanted with Ar and C ions, has been utilized to test the sensitivity of the 57 Fe eMS technique to the different types of defects generated by the different ion species. The dominant feature of the Mössbauer spectrum of the Ar implanted ZnO sample was a magnetic hyperfine field distribution component, attributed to paramagnetic Fe 3+ , while that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(25 reference statements)
0
6
0
Order By: Relevance
“… 15 and Bharath-Ram et al . 70 investigated C-doped and C ion implanted ZnO system. They proposed that the C ions replace O site and results in Zn-C system.…”
Section: Resultsmentioning
confidence: 99%
“… 15 and Bharath-Ram et al . 70 investigated C-doped and C ion implanted ZnO system. They proposed that the C ions replace O site and results in Zn-C system.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that it was a 0 2 + state and with a spherical shape as the 30 Mg ground state [48]. This means shape coexistence between spherical and deformed 0 + states in 32 Mg.…”
Section: Picking Flowers In the Nuclear Landscapementioning
confidence: 98%
“…The first target material used for production of Ar isotopes was vanadium carbide, VC, which resulted in the first observation of a T z = −2 isotope, 32 Ar [13]. By replacing the VC matrix with CaO powder an increase by a factor 1000 in the production yield was obtained [14].…”
Section: Isolde Target-ion-sources and Produced Radioactive Beamsmentioning
confidence: 99%
See 2 more Smart Citations